Opportunities and Threats for Vietnamese Brand Chilli Sauce Products - Hoang, Thanh Tung; Huynh, Tri Nang; Nguyen, Duc Duy (International Journal of Scientific Research and Management (IJSRM), 2024)
The article examines the characteristics that make Vietnamese chilli sauce products stand out, and the formation and development of some strong chilli sauce brands leading the Vietnamese chilli sauce market today. At the same time, the article points out opportunities and threats for Vietnamese brand chilli sauce products. Among them, opportunities for the development of Vietnamese chilli sauce products: (i) High consumer demand; (ii) Vietnamese chilli sauce businesses understand the domestic market; (iii) Local and international culinary trends; (iv) Effective marketing strategy; (v) Cooperation and association; (vi) Affirming brand and reputation in the food industry; (vii) Actively participate in fairs and exhibitions in world markets; (viii) Take advantage of e-commerce channels to compete domestically and bring products to the world market. Besides, the article also points out the threats facing the Vietnamese chilli sauce brand: (i) Consumer psychology; (ii) Fierce competition with foreign brands; (iii) Differences in principles for building food standards between countries when bringing chilli sauce products to the world market; (iv) Standards are increasingly strict for the food industry. The research results are the basis for the research team to consider and propose solutions from the government/associations and businesses to develop Vietnamese chilli sauce brands.